CO2-induced shift in microbial activity affects carbon trapping and water quality in anoxic bioreactors - Kirk, Matthew F.; Santillan, Eugenio F. U.; Sanford, Robert A.; Altman, Susan J. (My University, 2013)
Microbial activity is a potentially important yet poorly understood control on the fate and environmental impact of CO[subscript 2] that leaks into aquifers from deep storage reservoirs. In this study we examine how variation in CO[subscript 2] abundance affected competition between Fe(III) and SO[subscript 4]²ˉ-reducers in anoxic bioreactors inoculated with a mixed-microbial community from a freshwater aquifer. We performed two sets of experiments: one with low CO[subscript 2] partial pressure (~0.02 atm) in the headspace of the reactors and one with high CO[subscript 2] partial pressure (~1 atm). A fluid residence time of 35 days was maintained in the reactors by replacing one-fifth of the aqueous volume with fresh medium every seven days. The aqueous medium was composed of groundwater amended with small amounts of acetate (250 μM), phosphate (1 μM), and ammonium (50 μM) to stimulate microbial activity. Synthetic goethite (1 mmol) andSO[subscript 4]²ˉ (500 μM influent concentration) were also available in each reactor to serve as electron acceptors. Results of this study show that higher CO[subscript 2] abundance increased the ability of Fe(III) reducers to compete with SO[subscript 4]²ˉ reducers, leading to significant shifts in CO[subscript 2] trapping and water quality. Mass-balance calculations and pyrosequencing results demonstrate that SO[subscript 4]²ˉ reducers were dominant in reactors with low CO[subscript 2] content. They consumed 85% of the acetate after acetate consumption reached steady state while Fe(III) reducers consumed only 15% on average. In contrast, Fe(III) reducers were dominant during that same interval in reactors with high CO[subscript 2] content, consuming at least 90% of the acetate while SO[subscript 4]²ˉ reducers consumed a negligible amount (<1%). The higher rate of Fe(III) reduction in the high-CO[subscript 2] bioreactors enhanced CO[subscript 2] solubility trapping relative to the low-CO[subscript 2] bioreactors by increasing alkalinity generation (6X). Hence, the shift in microbial activity we observed was a positive feedback on CO[subscript 2] trapping. More rapid Fe(III) reduction degraded water quality, however, by leading to high Fe(II) concentration.
Keywords: Geological carbon storage; CO2 leakage; Iron reduction; Sulfate reduction; Microbial reaction rates; Groundwater; Pyrosequencing